Accuracy of ultrasound in prediction of rectosigmoid infiltration in epithelial ovarian cancer. (3rd October 2017) - Zikan, M.; Fischerova, D.; Semeradova, I.; Slama, J.; Dundr, P.; Weinberger, V.; Dusek, L.; Cibula, D.
ABSTRACT: Objective: To examine prospectively the accuracy of ultrasound in predicting rectosigmoid tumor infiltration in patients with epithelial ovarian cancer. Methods: Patients referred for a suspicious pelvic mass between 2012 and 2014 were examined by ultrasound following the standard protocol for assessment of tumor infiltration. Of the 245 patients examined, 191 had proven ovarian cancer and underwent primary surgery and were included in the analysis. Patients with apparently benign or inoperable disease were excluded. Rectosigmoid infiltration was evaluated by histopathology or according to perioperative findings. Clinical, pathological and laboratory parameters were analyzed as factors potentially affecting the sensitivity and specificity of sonography. Results: The sensitivity of ultrasound in detecting rectosigmoid infiltration in patients with ovarian cancer was 86.3%, with specificity of 95.8%, positive predictive value of 92.6%, negative predictive value of 91.9% and overall accuracy of 92.1%. Conclusion: Ultrasound is a highly accurate method for detecting rectosigmoid tumor infiltration in ovarian cancer patients, and thus, can be used for planning adequate management, including patient consultation, surgical team planning, suitable operating time and postoperative care. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd.